Reducing Bullwhip Effect in Fresh Food Vegetable Supply Chain Management: A strategic approach for Inclusive Growth - Somashekhar C. Iyanahally; Dr. J.K.Raju Raju; Dr. Hema Patil (International Journal of Supply Chain Management, 2013)
Inclusive growth is the mantra for a countrys growth. Inclusive growth itself demands inclusive support from all the sectors of industry and agriculture. But economy of industry and agriculture growth depends on proper supply of goods and food items to the ultimate consumers at right place, right time, right quantity with right price based on effective prediction or judgement of demand. The failure to predict proper demand by a company leads to fluctuation of demand between supply chain stages. This extends to bullwhip effect, which is a threat for economic growth. Nowadays Indian retailing industry is booming with more opportunities and has got increased contribution to the growth of economy. Due to the impact of globalization, Indian retailing formats are seeing metamorphosis. Retailing is getting transformed like India from unorganized to semi organized and organized retailing. Retailing in fresh food vegetable supply is slowly gaining importance in the agricultural based economy. Reaching the fresh food to vast country like India without proper supply chain and infrastructure is a daunting task. Balancing the demand and supply between semi-organized fresh food vegetable (SOFFV) retailers and fresh food suppliers amongst the supply chain activities is a challenging job. Using conjoint analysis this research focuses on different levels of combination of attributes preferred by the semi organized vegetables retailers, based on demand to identify fresh food delivery package with best utility rate. This article helps to understand the efficiency of information sharing to reduce the bullwhip effect.